Hybrid Social Security System – Integrating the Islamic Mutual (Khairat) benevolent and bereavement scheme with SOCSO social security system for self employed e-hailing workers / Radduan Yusof ... [et al.] - Yusof, Radduan; Abd Samad, Suhaimi; Zainuddin, Azizan; Hj Md. Shahid, Khairiyah (2021)
For many years, social security has become a very effective source of protection available for the formal sector workers. A sustainable and stable income with a mandatory contribution to the social security system makes every formal sector worker covered by proper social protection. Unfortunately, the emergence of the GIG economy had shown a tremendous impact on the labour force when it seemed to disrupt the employee-employer relation in the workforce. The side effect of this current scenario leads to the hike of informal sector workers such as e-hailing workers with the absence of adequate formal social security coverage. To address this issue, Social Security Organization Malaysia (SOCSO) has introduced Self-employment Social Security Scheme in 2017. However, it remains less popular among self-employed workers, probably due to lack of awareness and the inability to pay the yearly or monthly social security contribution. Forty-six respondents among e-hailing workers participated in this survey through google forms. It is found that most respondents are willing to contribute to this proposed Hybrid system with minimum contribution by automated deduction through SOCSO. Thus, an affordable social protection scheme proposed by this paper called as "Hybrid Social Security System – An Integrated the Islamic Mutual (Khairat) Benevolent and Bereavement Scheme with Social Insurance Scheme for Self Employed E-Hailing Workers" is one of the best options for this group of workers to achieve social inclusion as stipulated in Sustainable Development Goals by United Nations.